Using Individual Assessments as a Tool for Formative Feedback on Emotional Intelligence Training Programs in Healthcare Learners. (April 2022) - Chandrapal, Jason; Park, Chan; Holtschneider, Mary; Doty, Joe; Taylor, Dean
Introduction: Emotional Intelligence (EI) is a skillset that influences and impacts an individual's ability to create, foster, and maintain strong relationships. In healthcare settings optimal patient centered care exists when teamwork, critical thinking, selfless service, integrity, and emotional intelligence are effectively practiced. While various methods exist to teach EI in the preprofessional and professional settings, the assessment of the efficacy of these types of training remains elusive. We propose a novel use of EI assessments to determine the effectiveness of EI programs and suggest that the information obtained can help shape and improve future EI education. Methods: Volunteer participants involved in the 2020–2021 Feagin Leadership Program (FLP) at Duke University were recruited for this study. FLP is a one year program that aims to train healthcare leadership skills, with a special emphasis on EI. It is comprised of various stages of healthcare learners with a desire to improve their healthcare leadership skills. All participants took both an EI self-assessment (SSEIT) and EI ability assessment (MSCEIT) both before and after a dedicated 5-hour EI educational session. Individuals must have completed both a pre- and post-test for at least one assessment to be included in the study. Apart from standard descriptive statistics, Wilcoxon sign rank tests were utilized to determine the effectiveness of the educational session by comparing pre- and post-tests within each assessment. A Spearman's rank correlation coefficient was used to compare the results of the SSEIT and MSCEIT. Results: A total of 32 FLP scholars initially participated in which 18 completed all assessments. Average age was 29 years old and consisted of medical students (n = 16), residents (n = 7), fellows (n = 7), advanced practice provider (n = 1) and a researcher (n = 1). Group analysis of the SSEIT pre and post scores were 131 (±13, range 98-149) and 136(± 13, 106-105), respectively which were statistically significant. Pre and post MSCEIT scores were 102 (±20, range 32-141) and 103 (±12, range 80-121), which were not significant. The EI branches with the highest score on each test was Managing Own Emotions and Understanding Emotions for the SSEIT and MSCEIT respectively while Perceiving Emotions was the lowest for both assessments. Comparison of the SSEIT and MSCEIT demonstrated a moderate correlation that was statistically significant. Discussion: In our study participants felt their EI improved following the EI educational session, however this did not appear translate into their actual ability. This could be a function of self-report bias or a limitation of the EI assessments. More studies in this space are needed to make this determination. Additionally, the strengths of this specific program were within the strategic use of emotions therefore in the future more attention should be placed on experiential use of emotions, specifically perceiving emotions. As EI education and training becomes more prevalent it is important to not only accurately assess an individual's EI ability but also the effectiveness of the education being presented. We propose that EI assessments can be utilized as a tool to measure the effectiveness of EI education and receive formative programmatic feedback.